Ergonomic Program and Nursing Intervention in Nursing Students - Prapti, Ni Ketut Guru; Nurhesti, Putu Oka Yuli; Tirtayasa, Ketut (Journal of A Sustainable Global South, 2020)
Ergonomics position is the position that should be done while working on a such procedure to improve work security, work efficiency and reduce risk factors. Nurses are the health workers with the biggest exposure risk factor. The results of the preliminary study showed that more than 50 percent of the students are still doing the wrong position when performing nursing interventions. This study was conducted at Nursing Study Program of Udayana University wich aims to know the effect of comprehensive ergonomic program on ergonomic position of students when performing nursing interventions. A quasy experimental design with action research application was used to analyze the effect of an ergonomic program on knowledge, attitude and behavior of nursing students. Nursing students of Udayana University was the population of this study and simple random sampling techniques was used with sample size of 50 respondents. Evaluation of this study were involves the readiness of institutions to apply programs and modifications according to institutional conditions. The results showed that there is a significant effect of ergonomic program on student's knowledge, attitude and behavior related to ergonomic standard in performing nursing interventions with statistic test result p <0,05. Student behavior can be improved by increasing the students' knowledge on the ergonomic position when performing nursing intervention. Based on the results of this study, the institute is expected to provide knowledge about the importance of ergonomics position to nursing students, either through counseling or by incorporating into one of the subjects in the nursing curriculum. Index Terms — ergonomic program, nursing student and nursing intervention